2000
DOI: 10.1177/002795010017100107
|View full text |Cite
|
Sign up to set email alerts
|

How Well Can We Measure Graduate Over- Education and Its Effects?

Abstract: Using data from two cohorts of graduates, this article examines three aspects of over-education. First, using three new measures, we present an estimate of graduate over-education in the UK. We find that the scale of over-education varies with measurement techniques, with weak correlations between the three measures. Second, across the three measures we estimate the effects of over-education on earnings and job satisfaction. The effects of over-education on earnings and job satisfaction are similar, not withst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
113
1
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(125 citation statements)
references
References 23 publications
6
113
1
5
Order By: Relevance
“…They generally indicate that over-educated workers have a lower level of job satisfaction, receive less training and are more likely to quit their jobs than their adequately educated former classmates, i.e. individuals with the same attained education (Ahn et al, 2001, Allen and van der Velden, 2001, Battu et al, 2000, Büchel and Mertens, 2004, Feldman and Turnley, 1995, Sicherman, 1991, Tsang, 1987, van Smoorenburg and van der Velden, 2000, Verhaest and Omey, 2006, Vieira, 2005. These results suggest that over-education is likely to induce negative productivity costs for firms (due to higher turnover rates) and the overall economy (due to a lower level of job satisfaction and less training participation).…”
Section: Introductionmentioning
confidence: 99%
“…They generally indicate that over-educated workers have a lower level of job satisfaction, receive less training and are more likely to quit their jobs than their adequately educated former classmates, i.e. individuals with the same attained education (Ahn et al, 2001, Allen and van der Velden, 2001, Battu et al, 2000, Büchel and Mertens, 2004, Feldman and Turnley, 1995, Sicherman, 1991, Tsang, 1987, van Smoorenburg and van der Velden, 2000, Verhaest and Omey, 2006, Vieira, 2005. These results suggest that over-education is likely to induce negative productivity costs for firms (due to higher turnover rates) and the overall economy (due to a lower level of job satisfaction and less training participation).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Hersch (1991) found for the US that over-educated workers were less satisfied than adequately educated workers and (1995) that over-educated workers received less on-the-job training, but were more likely to be promoted. Yet Battu et al (2000) found a negative relationship between over-education and promotion for UK graduates and no evidence of employers upgrading tasks given to the over-educated. The same authors (1999) found that over-educated graduates had significantly lower job satisfaction than those who were in graduate-level jobs.…”
Section: A) the Effect Of Training On Job Satisfactionmentioning
confidence: 87%
“…The first 'subjective' approach uses self-assessment to define the job's educational requirements and then compares this with the worker's actual education (Battu, Belfield and Sloane 2000;McGuinness 2003). The second is a variation on the above and involves asking the worker directly whether he or she is overeducated (Devillanova 2012).…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%